2022
DOI: 10.1021/acs.iecr.2c00596
|View full text |Cite
|
Sign up to set email alerts
|

Double-Accessible Open Metal Sites in Metal–Organic Frameworks with Suitable Pore Size for Efficient Xe/Kr Separation

Abstract: The separation of a Xe/Kr mixture is an industrially important but challenging process due to their inherent inert nature and similar atomic sizes. Porous materials containing open metal sites have been extensively proved to be an effective strategy for the Xe/Kr capture and separation. However, conventional materials with single open metal sites display the limitations of gas uptake at low pressure and separation selectivity of a Xe/Kr mixture. Herein M(pz)[Ni(CN) 4 ], simplify as MpzNi (M = Co, Ni, pz = pyra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…Remarkably, Ni(IN) 2 exhibited the highest adsorption of Xe at 0.2 bar among the reported MOF adsorbents, such as CopzNi (58.69 cm 3 g −1 ), Ni 2 ( m -dobpdc) (58.12 cm 3 g −1 ), MOF-Cu–H (58.27 cm 3 g −1 ), Zn(ox) 0.5 trz (45.91 cm 3 g −1 ) and SIFSIX-3-Zn (41.51 cm 3 g −1 ). 11,26–29 Considering the Xe/Kr selectivity and Xe uptake at 0.2 bar, we found that Ni(IN) 2 and Ni(AIN) 2 were located in an ideal region of performance diagram (Fig. 2f and Table S8†).…”
Section: Resultsmentioning
confidence: 90%
“…Remarkably, Ni(IN) 2 exhibited the highest adsorption of Xe at 0.2 bar among the reported MOF adsorbents, such as CopzNi (58.69 cm 3 g −1 ), Ni 2 ( m -dobpdc) (58.12 cm 3 g −1 ), MOF-Cu–H (58.27 cm 3 g −1 ), Zn(ox) 0.5 trz (45.91 cm 3 g −1 ) and SIFSIX-3-Zn (41.51 cm 3 g −1 ). 11,26–29 Considering the Xe/Kr selectivity and Xe uptake at 0.2 bar, we found that Ni(IN) 2 and Ni(AIN) 2 were located in an ideal region of performance diagram (Fig. 2f and Table S8†).…”
Section: Resultsmentioning
confidence: 90%